Analisis Kelayakan Investasi Pada Sektor Industri Jasa Sewa Alat Berat Menggunakan Skema Pendekatan BMC - Budiarjo, Akhmad; Syairudin, Bambang (GEMA EKONOMI, 2023)
Accelerated development is a government strategy, this is done to reduce social inequality between regions. The government, through "Presidential Regulation no. 80 of 2019" concerning the acceleration of development encouraged East Java by disbursing Rp 294.3 trillion to realize national strategic projects. This is done to accelerate the economic turnover in East Java.The number of projects that are being worked on, entrepreneurs consider it a good opportunity to try a business in the heavy equipment rental service industry sector. Before an investor makes a decision to invest, he should look at these opportunities from several business sectors so that he can get benefits in the future.The application of the right business model will make the heavy equipment rental business run as expected, from a financial point of view it can be controlled properly. The right business model for running a heavy equipment rental business is Business model cavas, which is a strategic management tool for defining and communicating ideas or concepts quickly and easily. After the business model is created, it is necessary to analyze it from a financial point of view by applying the BMC scheme that has been made. It aims to see whether the business is feasible or not feasible to be realized. However, in starting the establishment of a heavy equipment rental service business entity, it is necessary to focus on certain types of heavy equipment in order to maximize marketing and sharpen knowledge of these knowledge products.In this research, the decision of the type of heavy equipment selected is based on data from the POKJA and observation and compiles the two data. After compiling, the most relevant dump truck type heavy equipment in East Java is obtained, where the heavy equipment is most widely used in project planning in East Java. Furthermore, the establishment of dump truck rental services will be assessed from a financial point of view to find out whether it is feasible or not feasible for the business to run by applying the BMC scheme that has been made. The results of the financial analysis obtained, from the point of view of the level of investment risk, are: NPV of Rp 26,992,279,788 and PI value of 1.29. From the point of view of the rate of return on investment: IRR value of 18.13% and return on investment based on PP for 6 years and 5 months. Therefore, the establishment of a heavy equipment rental service business entity with the BMC approach scheme is "feasible to run".